E-learning at UNIMAS : students' acceptance of morpheus for teaching and learning - Ang, Wei Sook. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The rapid growth of the e-Iearning market has drawn much discussion about the learners' acceptance of various e-Iearning systems. The acceptance of e-Iearning platform among UNIMAS students need to be determined so that instructors can have better understanding of students' perception. The objective of this research is to investigate UNIMAS students' acceptance towards the use of the e-Iearning system adopted by the university for teaching and learning. UNIMAS chose MoodIe as Learning Management System (LMS) and started to implement since year 2006, named as Morpheus. In order to examine lTNIMAS students' acceptance towards e-Iearning system, Technology Acceptance Model (TAM) is used in this research as the theoretical framework. The research design used was survey research which focuses on cross-sectional research. The respondents were the UNIMAS students from eight faculties who have been selected randomly according to actively using Morpheus courses in academic semester 2010/2011, semester 1. 120 questionnaires were distributed and there are 105 questionnaires with complete data were collected with respondents' demographic information, perceived ease of use, perceived usefulness and intention to use towards the elearning system. The degree of students' acceptance is measured by computing the mean of perceived ease of use and the mean of perceived usefulness. The findings showed there are high perceived usefulness and high perceived ease of use towards usage of Morpheus at UNIMAS. Furthermore, findings also showed there is no significant difference in students' acceptance of the usage of Morpheus based on gender and technology access location. On the other hand, fmdings showed there is significant difference in students' acceptance based on frequency of usage and academic achievement. Future researches are recommended to investigate the challenges and barriers of e-Iearning at UNIMAS as well as comparing the acceptance of e-Iearning in UNIMAS with other universities.